Florida 4-H Horse Member Advancement Program Level III - Edward L. Johnson; R. L. Horton; Nancy Johnson (EDIS)
This program is designed to help members improve their understanding of horses and horse care, advance their skills in riding and handling horses, provide goals for leading, make their 4-H horse experiences more interesting and enjoyable, and let them progress at their own speeds while challenging them to keep working to become better horsemen and 4-H members. This document is 4HHSM52 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published 1989. Reviewed June 2002.